Which Soft? : decision support software - Tereso, Anabela Pereira (2011)
In this project we developed a decision support software that helps to choose the best decision software, but can also be applied to any other problem of selection. It is based on multicriteria methods. With this software we try to give each user the best solution, depending on his preferences. The entire project was planned and outlined in UML, implemented in C# and the database was built with SQL Server. It was a project divided into three main stages: requirements gathering, UML specification and implementation phase.